Crystallization Kinetics of Hypo, Hyper and Eutectic Ni–Nb Glassy Alloys - Mendoza, Laura Esmeralda; Hernández Soto, José Manuel; González, José Gonzalo; Orgaz, Emilio; Lozada, Octavio; Figueroa, Ignacio Alejandro (My University, 2022)
This study presents the thermal and kinetic behavior of Ni58.5 Nb41.5, Ni59.5 Nb40.5, and Ni60.5 Nb39.5 binary glassy alloys. The alloys ingots were obtained through an electric arc furnace and the ribbons using the melt-spinning technique at two different wheel speeds, 8 and 25 m/s. The non-isothermal study was carried out by means of Differential Scanning Calorimetry (DSC) at five different heating rates: 12.5, 15, 17.5, 20, and 22.5 K/min. X-ray Diffraction (XRD) analysis showed a fully glassy phase for all ribbons for all compositions. For both wheel speeds, the ribbons with higher Nb content were significantly thinner than those with less content. The activation energies were calculated from the Kissinger method, showing the tendency Ep1 >Ex1 >Eg, where Ep1, Ex and Eg denote the activation energies of first peak temperature, the first crystallization onset and glass transition, respectively. The Flynn–Wall–Ozawa model displayed a close correlation with heating rates, ribbon thicknesses, and composition. The Nb content enhanced the glassy stability since the activation energy required for crystallization increased at higher Nb concentrations. © 2022 by the authors. Licensee MDPI, Basel, Switzerland.